The Role of Rationality in Metaethics - Farrux Usmonov (Web of Scientist International Scientific Research Journal, 2025)
The article explores the role of rationality in metaethics, focusing on how reason shapes moral judgments, ethical language, and normative justification. It examines various philosophical perspectives on the relationship between rational thought and moral values, highlighting the debates between cognitivist and non-cognitivist approaches. The study emphasizes that rationality serves as a crucial tool for analyzing moral concepts, resolving ethical dilemmas, and evaluating the consistency of moral beliefs. By situating rationality at the core of metaethical inquiry, the article underscores its significance in understanding the foundations of moral discourse and decision-making